Is the Angiostrongylus vasorum infection in domestic dogs underestimated or misdiagnosed? A comprehensive presentation of four lethal cases - Taulescu, Marian Aurel; Negoescu, Andrada; Ungur, Andrei; Toma, Corina; Ionică, Angela Monica; Gal, Claudiu; Sandu, Ioana; Buzdea, Alexandru; Tutuneanu, Andrei; Turcitu, Mihai; Horvat, Ioan Emilian; Deak, Georgiana (Frontiers in Veterinary Science, 2023)
Angiostrongylus vasorum (A. vasorum) is a widely distributed gastropod-borne nematode, causing severe cardio-pulmonary disorders in dogs. In Romania, A. vasorum was detected in foxes and serologically confirmed in domestic dogs, but no clinical cases are currently diagnosed. Four dogs with clinical history of respiratory distress, originating from different geographical regions of Romania, were included in the study. One dog (case 1) was clinically evaluated using thoracic radiology and cardiac ultrasound; examination of faeces and PCR were also performed for the etiologic diagnosis. The postmortem exam was performed in the other three cases, followed by parasitological and molecular analyses. In the first case, parasitic pneumonia was suspected based on the radiographic examination of the thorax and the infection with A. vasorum was confirmed by L1 morphological identification and PCR. The main postmortem changes included large, coalescing, dark red areas of pulmonary consolidation (n=3) and numerous adult nematodes in the pulmonary arteries (n=2). The histopathological examination of the lungs showed necrotizing and granulomatous pneumonia with severe hemorrhages and chronic pulmonary arterial changes. Intralesional nematodes were seen in all necropsied cases. Additional inflammatory changes related to A. vasorum infection were identified in the brain and tracheobronchial and mediastinal lymph nodes (n=2). Identification of larvae, histopathology and PCR confirmed the infection with A. vasorum. This study describes the first cases of canine cardiopulmonary angiostrongylosis in domestic dogs in Romania, and focuses on clinical presentation, pathological findings and molecular analysis. Angiostrongylosis should be included on the list of differential diagnoses of canine cardiopulmonary distress and/ or haemorrhagic diathesis in Romania and awareness should be raised among clinicians to avoid post-mortem diagnosis in the future.